Legal Settlement of The Crime of Desertion in Absentia in The Jurisdiction of Military Court I-02 - Nainggolan, Yolanda; Esther, July (Manunggal Halim Jaya, 2025)
One type of criminal offense that is often committed by Indonesian National Army (TNI) Soldiers is the crime of desertion as regulated in Law Number 39 of 1947 concerning the Military Criminal Code (KUHPM) precisely in Article 87 which is an act committed by a TNI Soldier to leave military service without superior permission, at a specified time and place. The crime of desertion has the main characteristic of unauthorized absence committed by an army person at a place. The absence can be in the form of traveling to a place, hiding oneself, crossing the enemy, entering the military service of another country, or deliberately making oneself left behind. The settlement of cases of desertion crimes often finds several problems, one of which is that the person who committed the crime of desertion cannot be found, which causes the examination process to be carried out in the absence of the defendant (In Absentia). In Absentia, an examination is carried out so that the case is resolved quickly to uphold the discipline of soldiers and maintain the integrity of the troops. Including the case of the case submission that was not examined because from the beginning, the defendant fled and was not found again within 6 (six) consecutive months from the date of submission of the case file and 3 (three) consecutive summons efforts have been made. An examination can be conducted and decided without the defendant's presence in court.